Ivabradine Reduces Digitalis‐induced Ventricular Arrhythmias. Issue 6 (10th July 2017) - Frommeyer, Gerrit; Weller, Jan; Ellermann, Christian; Bögeholz, Nils; Leitz, Patrick; Dechering, Dirk G.; Kochhäuser, Simon; Wasmer, Kristina; Eckardt, Lars
Abstract: The I (f) channel inhibitor ivabradine is recommended for treatment of heart failure but also affects potassium currents and thereby prolongs ventricular repolarization. The aim of this study was to examine the electrophysiological effects of ivabradine on digitalis‐induced ventricular arrhythmias. Thirteen rabbit hearts were isolated and Langendorff‐perfused. After obtaining baseline data, the digitalis glycoside ouabain was infused (0.2 μM). Monophasic action potentials and ECG showed a significant abbreviation of QT interval (−34 ms, p < 0.05) and action potential duration (APD90 ; −27 ms, p < 0.05). The shortening of ventricular repolarization was accompanied by a reduction in effective refractory period (ERP; −27 ms, p < 0.05). Thereafter, hearts were additionally treated with ivabradine (5 μM). Of note, this did not exert significant effects on QT interval (−4 ms, p = ns) or APD90 (−15 ms, p = ns) but resulted in an increase in ERP (+17 ms, p < 0.05). This led to a significant increase in post‐repolarization refractoriness (PRR, +32 ms, p < 0.01) as compared with sole ouabain treatment. Under baseline conditions, ventricular fibrillation (VF) was inducible by a standardized pacing protocol including programmed stimulation and burst stimulation in four of 13 hearts (31%; 15 episodes). After application of 0.2 μM ouabain, eight of 13 hearts were inducible (62%, 49 episodes). Additional infusion of 5 μM ivabradine led to a significant suppression of VF. Only four episodes could be induced in two of 13 hearts (15%). In this study, ivabradine reduced digitalis‐induced ventricular arrhythmias. Ivabradine did not affect ventricular repolarization in the presence of digitalis treatment but demonstrated potent anti‐arrhythmic properties based on an increase in both ERP and PRR. The study further characterizes the beneficial electrophysiological profile of ivabradine.